2010
DOI: 10.1214/09-aop523
|View full text |Cite
|
Sign up to set email alerts
|

A change of variable formula with Itô correction term

Abstract: We consider the solution u(x, t) to a stochastic heat equation. For fixed x, the process F (t) = u(x, t) has a nontrivial quartic variation. It follows that F is not a semimartingale, so a stochastic integral with respect to F cannot be defined in the classical Itô sense. We show that for sufficiently differentiable functions g(x, t), a stochastic integral g(F (t), t) dF (t) exists as a limit of discrete, midpoint-style Riemann sums, where the limit is taken in distribution in the Skorokhod space of cadlag fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(59 citation statements)
references
References 15 publications
2
55
0
2
Order By: Relevance
“…In [4], Coutin and Qian have shown that the rough paths theory of Lyons [13] can be applied to the 2D fractional Brownian motion B = (B (1) , B (2) ) under the condition that its Hurst parameter H (supposed to be the same for the two components) is strictly bigger than 1/4. Since this seminal work, several authors have recovered this fact by using different routes (see e.g.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In [4], Coutin and Qian have shown that the rough paths theory of Lyons [13] can be applied to the 2D fractional Brownian motion B = (B (1) , B (2) ) under the condition that its Hurst parameter H (supposed to be the same for the two components) is strictly bigger than 1/4. Since this seminal work, several authors have recovered this fact by using different routes (see e.g.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…We refer to [11] for an exhaustive study of this notion. Now, let us introduce the following object: (1) k/n , B (2) k/n ) + ∂f ∂x (B (1) (k+1)/n , B (2) k/n ) 2 B (1) (k+1)/n − B (1) k/n + nt −1 k=0 ∂f ∂y (B (1) k/n , B (2) k/n ) + ∂f ∂y (B (1) k/n , B (2) (k+1)/n ) 2 B (2) (k+1)/n − B (2) k/n . (1.1) If I n (t) defined by (1.1) does not converge in probability but converges stably, we denote the limit by…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 'Midpoint' sum, ⌊ can be shown to converge in probability for fBm with H > 1/4 (see [11]). The end point case H = 1/4 was considered in papers by Burdzy and Swanson [1], and Nourdin and Réveillac [7]. These papers proved the change-of-variable formula…”
Section: Introductionmentioning
confidence: 92%
“…For some T > 0, let B = {B H t , 0 ≤ t ≤ T } be a fractional Brownian motion with Hurst parameter H. That is, B is a centered Gaussian process with covariance R(s, t) given in (1). Let E denote the set of R-valued step functions on [0, T ].…”
Section: Fractional Brownian Motionmentioning
confidence: 99%